Education for elderly people in pandemic time in The Núcleo de Estudos da Terceira Idade: experience report (Olhar de Professor, 2021)
The COVID-19 pandemic raised the need for reformulations in educational processes, especially for the elderly. Social distance and education through digital technologies were became necessary. This report presents the strategy of maintaining the link with the elderly students of the Núcleo de Estudos da Terceira Idade (NETI) with the proposal of the “Quarantine Program at NETI”. The program consists of weekly messages of different materials and content in WhatsApp groups of the activities offered. The program was evaluated by elderly students through an online questionnaire, which 96.7% showed great satisfaction and satisfaction with the materials. The materials address different contents, themes and formats, and the videos are the favorite option for the elderly students. In conclusion, the program has been a successful experience since it has provided links with the elderly students and the sharing of information during the COVID-19 pandemic.
Keywords: Education. COVID-19. Elderly.